2013
DOI: 10.1128/jvi.01085-13
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cross-Reactive Antibodies to Novel H7N9 Influenza Virus by Recombinant Newcastle Disease Virus Expressing a North American Lineage H7 Subtype Hemagglutinin

Abstract: Severe human disease caused by the emerging H7N9 influenza virus in China warrants a rapid response. Here, we present a recombinant Newcastle disease virus expressing a North American lineage H7 influenza virus hemagglutinin. Sera from immunized mice were cross-reactive to a broad range of H7 subtype viruses and inhibited hemagglutination by the novel H7 hemagglutinin. Immunized mice were protected against a heterologous H7 subtype challenge, and genetic analysis suggested that cross-protective antibodies reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 27 publications
6
46
0
Order By: Relevance
“…These results and recent reports from other groups show that there is substantial cross-reactivity between H7 strains in mice and humans (20,(36)(37)(38)(39) but to a much lesser extent in ferrets (24). This cross-reactivity is most likely induced by antibodies against antigenic site A, which is highly conserved in avian H7 isolates.…”
Section: Discussionsupporting
confidence: 65%
“…These results and recent reports from other groups show that there is substantial cross-reactivity between H7 strains in mice and humans (20,(36)(37)(38)(39) but to a much lesser extent in ferrets (24). This cross-reactivity is most likely induced by antibodies against antigenic site A, which is highly conserved in avian H7 isolates.…”
Section: Discussionsupporting
confidence: 65%
“…Here we chose to express the HA and NA proteins from two isolates of the novel Chinese H7N9 influenza virus, A/Anhui/1/13 and A/ Shanghai/1/13 20,21 . These are timely examples, but the described protocol can be used for expression of any influenza A and B HA or NA proteins and can be adapted to express any other secreted viral or cellular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that ferret antiserum against these H7 ca viruses had cross-reactivity to the H7N9 virus (30). The cross-reactivity between divergent H7 viruses was also reported for the inactivated virus, recombinant protein, or virus-like particle (VLP) vaccines studied in mice (31)(32)(33) or humans (34). Another Eurasian-lineage H7N3 LAIV reassortant with an alternative internal gene backbone was reported to induce cross-reactive antibodies to H7N9 (35), indicating that an H7 LAIV might be protective against a divergent H7 strain.…”
mentioning
confidence: 99%